Penelusuran Debit Anak Sungai Musi Berdasarkan Pengukuran Curah Hujan Kota Palembang: Discharge Routing of Musi River Tributary Based on Rainfall Measurements in Palembang City - Permatasari, Rosmalinda; Andayani, Reni; Umari, Zuul Fitriana (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2024)
The hydrological cycle of the South Sumatra region is influenced by the potential flow produced by the Musi River and its tributaries. The quantity of water that is accessible at any given place is never constant and varies with time. The primary input to the river basin simulation model is flow and discharge data, which must be a time series that completely captures the variability of river flow and discharge data in order to accurately depict water availability. Because the Sekanak River is one of the tributaries of the Musi River, the research built a hydrological model that combines rainfall and river discharge to determine the discharge. The monthly rainfall data is processed to obtain the average rainfall during the data analysis step. The modified Penman method is then used to calculate evapotranspiration. The FJ Mock model was used to examine the mainstay discharge. Results of the discharge analysis for the period of 2018 to 2022 using the FJ Mock method show that the largest discharge occurred between March and June, ranging from 0.203 to 0.241 m3/sec. When the calculated discharge and the actual discharge are compared, it can be seen that the minimum discharge happens in August and the maximum discharge typically occurs in March in the actual discharge data.